The Shift of Islamic Shari’a in Economy: Banks, Foreign Investment and the Ottoman Collapse - Desmadi Saharuddin; Meirison, Meirison; Mansoer, Masri; Surwati, Surwati; Muhammadi, Qasem (Nurani, 2025)
At the height of the Ottoman Empire's glory, there was no need for a usury system, as it was prohibited by Islamic law. This Empire stands on an independent economy in line with Islamic law. Military agitation was everywhere; debt after debt appeared and even forced to borrow by donor countries and persuaded by Germany when World War I was about to erupt. This study aims to examine the shift in the role of Islamic law in the economy during the shaky Ottoman government in 1855-1923. This research is library-based with a qualitative approach; the information gathered comes from reviewing literature or written sources, such as books and previous studies, which are then processed and interpreted descriptively. We found that Banking in the Ottoman Empire was unnecessary because it was also not profitable for the Ottomans at a critical time. On the other hand, donor countries will benefit. Turkey is conditioned to continue to be in debt in various ways, such as rebellions in the Balkans, the Crimean War, and the last is world war I. The Debt Collection Agency (OPDA) has functioned as a collector of surplus natural resources and medium-sized industries in Turkey without the approval of the Government. They consist of foreign bankers with printed money that is no longer controllable and causes inflation, not to mention the circulation of foreign currency. Turkey's stability ended after preventing the establishment of a Jewish state, the owner of the most considerable capital in Europe.This article discusses the potential dangers of foreign banks operating in a country, including risks to the local economy, financial stability, and national sovereignty.